SYNTHESIS, CHARACTERIZATION, AND APPLICATION OF MOLECULARLY IMPRINTED POLYMER FOR THE EXTRACTION OF SEVERAL TRIAZOLE ANTIFUNGALS IN BLOOD PLASMA - Gunawan, Untung
The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted life worldwide. Fungal coinfection is an emerging problem in the COVID-19 pandemic. The most common pathogens found were Aspergillus and Candida sp. Triazole antifungals are one of the first-line therapies for the prevention and treatment of invasive fungal infections. Therapeutic drug monitoring of triazole antifungal drugs is recommended to maximize therapeutic outcomes and minimize the risk of toxicity. The challenge in developing a bioanalytical method for triazole antifungals is sample preparation, which requires a selective extraction stage due to the complexity of biological matrices. Molecularly imprinted polymer (MIP) is one of the separation methods used to increase separation selectivity in complex matrices. This research aims to develop MIP for solid phase extraction, which simultaneously separates and enriches several triazole antifungals (voriconazole, itraconazole, and fluconazole) in blood plasma. The research was initiated with computational studies to observe the interactions between template molecules and functional monomers. The screening was carried out using 39 functional monomers that are commonly used in MIP synthesis. Acrylic acid, itaconic acid, acrylamide, and 2-hydroxyethyl methacrylate were the selected monomers to be used in laboratory study based on binding free energy from molecular docking, type of intermolecular interactions, complexation energy, and Gibbs free energy. The comparison of monomer concentrations showed that the higher the ratio of template molecules: functional monomer, the stronger bond was formed, with a ratio of 1:4 being the optimal ratio. Studies on porogen solvents revealed that acetonitrile was the optimal solvent for MIP synthesis. Determination of the association constant of triazoles antifungal as template molecules was conducted using four selected functional monomers from the computational study using the UV spectrophotometric titration method. The stoichiometry of the reaction between the triazole antifungal and the monomers was observed using the Job Plot method. The results indicated a strong bond between the template molecules and the functional monomer as indicated by the association constant values of acrylic acid, itaconic acid, acrylamide, and 2- hydroxyethyl methacrylate, respectively 1190.5, 881.4, 866.7, 765.9 for voriconazole, 1669.9, 339.9, 1314.9, 388.3 for itraconazole, and 1343.3, 976.6, 673.4, 785.1 M-1 for fluconazole. Acrylic acid was the monomer with the highest Ka value interacting with the template molecules. Job plot analysis demonstrated that the reaction stoichiometry between the template molecule and the functional monomers was 1:1. The synthesis optimization process was performed to functional monomers, porogen solvent, temperature, time, and stirring speed using precipitation and bulk polymerization. Optimal results were obtained using triazole antifungal as template molecules, acrylic acid as a monomer, EGDMA as a crosslinker, and AIBN as an initiator. In the synthesis, a combination of dichloromethane: acetonitrile (5:20) solvent was used as much as 250 mL for precipitation and 25 mL for bulk methods. The synthesis of MIP and non-imprinted polymer (NIP) was carried out at a temperature of 70ºC using an oven for the bulk method and an oil bath at a speed of 400 rpm for the precipitation method. The synthesis results established that precipitation provides a higher yield (71-91%) than the bulk method (67-75%). The template removal was carried out using the sonication method. MIP was added with a solvent and then sonicated for 30 minutes. The sonication results were centrifuged at 6000 rpm for 10 minutes. The supernatant was separated and monitored using a UV spectrophotometer, repeated until no more template molecule spectra were observed. Development and validation of a high-performance liquid chromatography (HPLC) method for simultaneous analysis of triazole antifungals was carried out to characterize the adsorption capability of MIP. Optimization of the HPLC system was carried out using the one-factor-at-time (OFAT) method. Optimization results indicated that the optimum separation was obtained with a C18 column with a length of 25 cm and a particle size of 5 ?m, using an isocratic elution system with a mobile phase of acetonitrile: water (70:30) with acetonitrile as a solvent, a flow rate of 1 mL/minute with an injection volume of 50 ?L, detection was carried out at a wavelength of 260 nm. The retention times for fluconazole, voriconazole, and itraconazole were 2.5, 3.5, and 9 minutes, respectively. The results of the HPLC system suitability test with the parameters of capacity factor, tailing factor, resolution, number of theoretical plates, and injection repeatability meet the requirements. Validation of the analytical method provides results that meet the acceptance requirements for the parameters of specificity, linearity, detection and quantitation limits, accuracy, and precision. An adsorption study was performed by optimizing the type of solvent, time, and polymer composition. Acetonitrile was the optimal solvent for adsorption; MIP synthesized by the precipitation method has better adsorption compared to the bulk method. MIP with multiple template molecules has better binding than MIP with a single template molecule. MIP with a ratio of 1:4:20 had the best binding compared to other ratios, with adsorption capacity values for fluconazole, voriconazole, and itraconazole were 2.19, 2.36, and 2.57 mg/g, respectively. Adsorption equilibrium was reached in 2 hours, and MIP adsorption followed pseudo-second-order kinetics. MIP follows the Freundlich isotherm for all template molecules. MIP was characterized using the fourier-transform infrared (FTIR), scanning electron microscope energy dispersive X-ray (SEM-EDX), thermogravimetric analysis (TGA), particle size analysis (PSA), and Brunauer–Emmett–Teller (BET). Characterization by FTIR showed that the template molecules were successfully extracted from the MIP, all of the peak markers were not observed. Characterization using SEM indicated that MIP and NIP synthesized using the precipitation method have a more homogeneous shape compared to the bulk method. The EDX results demonstrated that the template molecules have been completely removed from the MIP. The thermogram revealed that MIP has a spectrum similar to that of NIP after template removal, confirming the template molecule's successful extraction. The PSA results proved that MIP has a larger particle size than NIP. BET test results confirmed that MIP has a larger surface area than NIP due to the formation of the cavity for the adsorption of template molecules. The optimum MIP from the adsorption results that have been characterized was packaged into a solid phase extraction cartridge (MISPE), and NIP was packaged into a cartridge (NISPE) as a comparison. Optimization of the system, including conditioning, loading, washing, and eluting, was carried out to obtain the optimal separation system. Optimization results indicated methanol, acetonitrile, and water as conditioning solvents, acetonitrile:water (1:1) as sample loading, water was used as washing, and methanol as elution solvent. The extraction efficiencies for fluconazole, voriconazole, and itraconazole were 90.44%, 95.19%, and 97.81%, respectively. The optimized SPE system was applied to blood plasma samples. Blood plasma was added with standard triazole in a ratio of 1:5. The sample was homogenized for 2 minutes at a speed of 3000 rpm, then centrifuged at a speed of 13000 rpm for 10 minutes. The sample was loaded into the optimized MISPE system. The result provided that MISPE was more selective for the separation than NISPE and SPE C18 by recovery values for fluconazole, voriconazole, and itraconazole were 82.44, 86.19, and 90.81%, respectively. MISPE demonstrated selectivity for triazole antifungals compared to reference substances, amphotericin, dexamethasone, ketoconazole, and miconazole, with an ? value of 74.38, 18.37, 8.47, and 8.94, respectively.